THE IMPACT OF AI QUILLBOT IN IMPROVING STUDENT WRITING ABILITY TO WRITE ARGUMENTATIVE ESSAYS - Pratama, Yoga; Fridolini, Fridolini; Pitaloka, Roro Meifi (University of Kuningan, 2025)
The integration of Artificial Intelligence (AI) in language learning has transformed academic writing, particularly in English as a Foreign Language (EFL) contexts. AI-powered writing tools such as QuillBot offer real-time feedback, automated paraphrasing, and grammatical enhancements, potentially improving students’ writing proficiency. However, limited research explores the specific impact of QuillBot on argumentative essay writing in EFL classrooms. This study aims to examine the effectiveness of QuillBot in enhancing the writing skills of third-semester EFL students at Universitas Darma Persada, Indonesia. Using a quasi-experimental design, 60 students were divided into an experimental group (QuillBot-assisted learning) and a control group (traditional instruction). Pre-test and post-test essay scores were analyzed using SPSS 27.0 to assess improvements in structure, coherence, and grammar. The findings revealed that students using QuillBot showed significantly higher improvements in writing proficiency compared to those in the control group. The experimental group demonstrated enhanced argumentation, coherence, and grammatical accuracy, indicating that AI-assisted tools can be effective in fostering writing development. The study concludes that QuillBot is a valuable supplementary tool for EFL writing instruction, providing instant feedback and reducing students’ dependency on traditional teacher-led corrections. Educators are encouraged to integrate AI writing assistants into teaching methodologies to optimize learning outcomes. Future research should explore the long-term effects of AI-assisted writing on different writing genres and across diverse educational contexts.